Which T category of nasopharyngeal carcinoma may benefit most from volumetric modulated arc therapy compared with step and shoot intensity modulated radiation therapy. - Ying Sun; Rui Guo; Wen-Jing Yin; Ling-Long Tang; Xiao-Li Yu; Mo Chen; Zhen-Yu Qi; Meng-Zhong Liu; Jun Ma (PLoS ONE, 2013)
BACKGROUND:To compare volumetric modulated arc therapy (VMAT) with conventional step and shoot intensity modulated radiation therapy (s-IMRT) in nasopharyngeal carcinoma (NPC) patients, and identify which T category patient gains the maximum benefit from VMAT. METHODS:Fifty-two patients that randomly selected from 205 patients received VMAT at a single center were retrospectively replanned with s-IMRT. For a fair comparison, the planning target volume (PTV) coverage of the 2 plans was normalized to the same level. A standard planning constraint set was used; the constraints for the organs at risk (OARs) were individually adapted. The calculated doses to the PTV and OARs were compared for s-IMRT and VMAT plans generated using the Monaco treatment planning system. RESULTS:VMAT and s-IMRT plans had similar PTV coverage and OAR sparing within all T categories. However, in stratified analysis, VMAT plans lead to better or similar sparing of the OARs in early T category patients; and lead to poorer sparing of the OARs in advanced T category patients (P<0.05). VMAT shows significant advantages for low dose burden (P<0.05) compared with s-IMRT. The delivery time per fraction for VMAT (424±64 s) was shorter than s-IMRT (778 ± 126 s, p<0.01). CONCLUSIONS:VMAT provides similar dose coverage of the PTVs and similar/better normal tissue sparing in early T category NPC, and poorer OARs sparing in advanced T category NPC. And VMAT shows significant advantages for low dose burden and delivery time.